AN ERROR ANALYSIS OF SIMPLE PRESENT TENSE USAGE IN SPEAKING EXPLANATION TEXT OF SIXTH SEMESTER ENGLISH DEPARTMENT STUDENTS OF INSTITUT PENDIDIKAN TAPANULI SELATAN (IPTS) - Chairun Nisa Aritonang (JURNAL LINER (Language Intelligence and Educational Research), 2018)
The purpose of this study were to describe the error and to find the cause of the error made by the sixth semester English department students of Institut Pendidikan Tapanuli Selatan (IPTS) of simple present tense usage in speaking explanation text. This is a qualitative research with 9 students of sixth semester English department student of IPTS as informants. The data were collected through speaking performance that was observed, documented, and interviewed. The documentation was made into the transcript so the writer could analyzed students’ errors in grammar and vocabulary in speaking, observation was made to observe the students’ errors in fluency and pronunciation in speaking, and interview was to know the cause or factor of the students’ errors of simple present tense usage in speaking. The result of this study was most of the sixth semester English department students still got high percentage errors. They did not know clearly the usage of simple present tense and most of them also got problem in speaking. These were grammar, vocabulary, fluency, and pronunciation.